Becoming a primary mathematics specialist teacher - Donaldson, Gina.; Donaldson, Gina. (Abingdon, Oxon ; New York : Routledge, 2012)
"Becoming a Primary Mathematics Specialist Teacher challenges teachers to think about the role and impact of the Mathematics Specialist in changing staff, parents and children's attitudes to the subject in the primary school. It explores what we really mean by deep mathematical subject knowledge, explains key pedagogical approaches to teaching mathematics, and demonstrates how you can effectively mentor less experienced or confident colleagues to improve teaching and learning. Illustrated throughout with classroom-based examples, research findings and theoretical ideas, this book considers a wide range of issues including the use and application of mathematics, the utilisation of practical resources, and the principles of progression. It also considers some common misconceptions in mathematics, and offers scenarios and reflection activities at the end of each chapter. This supportive text is centred around three key themes of deep subject knowledge, pedagogical knowledge and the skills required for mentoring, coaching and supporting colleagues - features which the authors explore first from a theoretical perspective, and secondly through the context of specific mathematical topics taken from the primary curriculum. Becoming a Primary Mathematics Specialist Teacher supports primary mathematics teachers in their development as reflective practitioners, who can confidently challenge practice in their own classroom and move the whole school forward through collaborative professional development"--
Includes bibliographical references and index.
Keywords: Mathematics -- Study and teaching (Primary); Teacher effectiveness